2022
DOI: 10.1017/s1355617722000881
|View full text |Cite
|
Sign up to set email alerts
|

Rostral-middle locus coeruleus integrity and subjective cognitive decline in early old age

Abstract: Objectives: Abnormal tau, a hallmark Alzheimer’s disease (AD) pathology, may appear in the locus coeruleus (LC) decades before AD symptom onset. Reports of subjective cognitive decline are also often present prior to formal diagnosis. Yet, the relationship between LC structural integrity and subjective cognitive decline has remained unexplored. Here, we aimed to explore these potential associations. Methods: We examined 381 community-dwelling men (mean age = 67.58; SD = 2.62) in the Viet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 84 publications
1
4
0
Order By: Relevance
“…We found a positive association between rostral LC intensity and fluid, but not crystallized, cognition specific to older adults with above-average cognition. Related results have previously been reported by others (Bell et al, 2023;Clewett et al, 2015;Dahl et al, 2019Dahl et al, , 2023, though not with perfect alignment. Clewett et al, 2015 found a significant association between crystallized intelligence and overall LC intensity, Bell et al, 2023 found an significant association between subjective cognition and rostral LC intensity, and Dahl et al, 2019 found a significant association between memory performance and rostral LC intensity, and then in 2023 found that LC intensity significantly predicted future episodic memory performance.…”
Section: Discussionsupporting
confidence: 89%
“…We found a positive association between rostral LC intensity and fluid, but not crystallized, cognition specific to older adults with above-average cognition. Related results have previously been reported by others (Bell et al, 2023;Clewett et al, 2015;Dahl et al, 2019Dahl et al, , 2023, though not with perfect alignment. Clewett et al, 2015 found a significant association between crystallized intelligence and overall LC intensity, Bell et al, 2023 found an significant association between subjective cognition and rostral LC intensity, and Dahl et al, 2019 found a significant association between memory performance and rostral LC intensity, and then in 2023 found that LC intensity significantly predicted future episodic memory performance.…”
Section: Discussionsupporting
confidence: 89%
“…Each LC mask was then divided into different subregions (25% rostral, 50% medial and 25% caudal portions of the LC) ( Figure 1C ). Other studies investigating LC integrity in different clinical conditions also used subdivisions of the LC, based on the fact that the LC is topographically organized in regions composed of cells projecting to different areas of the brain ( Shibata et al, 2007 ; Dahl et al, 2019 ; Liu et al, 2020 ; Doppler et al, 2021 ; Calarco et al, 2022 ; Bell et al, 2023 ). It was suggested that the rostral part of the LC would project to the forebrain including the hippocampus, while the medial and caudal portions would project to the basal ganglia, cerebellum, and spinal cord ( Pickel et al, 1974 ; Satoh et al, 1977 ; Mason and Fibiger, 1979 ; Loughlin et al, 1986 ).…”
Section: Methodsmentioning
confidence: 99%
“…Models in which all cognitive and behavioral items are pooled together fit better with LC variability than the ones in which NA-dependent and independent ones are separated 2021 Giorgi et al [ 42 ] 3 T 53 71.7 (4.7) No association between LC signal and age is found 2021 Bachman et al [ 43 ] 3 T Y 67 E 229 72.3 (4.0) In elderlies, LC signal is directly associated with cortical thickness of frontoparietal cortex, belonging to cognitive neuronal network modulated by the LC-NA system 2021 Van Egroo et al [ 44 ] 7 T 72 65.2 (8.2) LC signal is not associated with global sleep quality, but with the amount of nocturnal awakening. This relationship is stronger in subjects with higher level of plasmatic pTau (always within the normal range) 2022 Elman et al [ 45 ] 3 T 435 62–71 LC signal is directly associated with structural complexity of the cortex (assessed through cortical DTI) but not with cortical thickness 2023 Bell et al [ 46 ] 3 T 381 (SCI) 67.6 (2.6) In SCI subjects, the rostral LC signal is directly associated with cognitive performances (memory, executive and visuospatial) 2023 Al Haddad et al [ 47 ] 3 T 152 53–86 No association between LC signal and age is found 2023 Van Egroo et al [ 48 ••] 7 T 99 59.9 (13.1) The rostral LC signal is negatively associated with plasmatic levels of pTau, while only limited or no correlations are ob...…”
Section: Lc Alteration In Ageing Is Not Harmless: Insight From Lc-mri...mentioning
confidence: 99%
“…Indeed, two studies, in which cognitively unimpaired elderlies were recruited after a detailed neurological and cognitive assessment and submitted to LC-MRI, failed to detect LC alterations with ageing in healthy subjects [ 42 , 47 ], as no inverse associations of the LC-MRI signal with age [ 42 , 47 ] or cognitive performances were found [ 42 ]. On the contrary, in more studies, an age-dependent reduction of LC signal in healthy elderlies was proposed [ 39 41 , 43 , 45 , 46 , 49 ••]. In particular, analysis of larger cohorts of subjects, in which the authors explored LC features across the entire lifespan, found that the LC signal progressively increases up to the 5th–6th decades of life and then starts to decrease in subsequent years [ 39 41 ].…”
Section: Lc Alteration In Ageing Is Not Harmless: Insight From Lc-mri...mentioning
confidence: 99%